Pengembangan Model Perkuliahan Berbasis Presentasi Youtube Prodi PGMI STAI Wali Sembilan Dalam Meningkatkan Kreativitas Mahasiswa - MASKUR maskur maskur; Rahardjo Raharjo; Abdul Rohman Rohman (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2023)
AbstractThis study is investigating the development of a lecture model based on YouTube presentation assignments; what is being built is a collaboration between presenting skills, video design abilities, and the ability to use the YouTube channel. The method employed is a Research and Development approach, which begins with an examination of the needs and challenges of the first-semester student class. The study design is then carried out in order to boost student creativity. Researchers conducted trials up to three times before the target was reached and satisfactory findings were obtained. Data was gathered through interviews, observations, documentation, and due diligence tests. After being evaluated, it was discovered that the findings of a study on the construction of YouTube task-based lecture models can boost students' creativity and ability to become future teachers. These talents will be able to not only instruct but also use YouTube as a medium and source in the future.